Enjoying Maine : lively stories about people and places from the seacoast to the north country, to the mountains, from fishermen to loggers, as enjoyed by Maine's favorite newspaper columnist - Caldwell, Bill. (Portland, Me. : G. Gannett Pub., 1977)
Short articles about the people, places, customs, and wildlife of Maine.
Originally published in the Portland Press-herald and the Maine Sunday telegram.
Maine author.
Keywords: Caldwell, Bill, -- 1919-2001.; Maine -- Social life and customs; Maine -- Description and travel